Lobbying Legislatures - Bennedsen, Morten; Feldmann, Sven E. (Journal of Political Economy, 2002)
We analyze informational lobbying in the context of a multimember legislature that decides on the allocation of a public good. First, we observe that a majoritarian legislature provides widely different incentives for interest groups to lobby than a single decision maker does. Second, we compare a decentralized legislature, such as the U.S. Congress, to a parliament with strong party cohesion. Congress’s decentralized nature allows the strategic formation of policy coalitions among high‐demand districts and the exclusion of low‐demand districts. This increases the incentive to provide information about districts’ demand relative to a legislature in which the governing coalition is fixed.